Easy access to alpha-aryl substituted gamma-ketophosphonates: lewis acid mediated reactions of 1,3-diketones with alpha-hydroxyphosphonates and tandem regioselective C-C bond cleavage - Pallikonda, Gangaram; Chakravarty, Manab; Sahoo, Manoj Kumar (Organic & Biomolecular Chemistry, 2014)
A range of alpha-aryl substituted gamma-ketophosphonates is synthesised by Lewis acid mediated reactions of 1,3-diketones and easily accessible, inexpensive benzylic alpha-hydroxyphosphonates in an operationally simple method under solvent-free conditions without exclusion of air/moisture. A regioselective C-C bond cleavage for 1,3-diketones in a tandem fashion has also been demonstrated. Synthesis of a gamma-ketophosphonate with phenol functionality at the a-position (structural analogue of raspberry ketone, a natural product) has also been presented.